The Role of Phospholipids and the Factor VII Gla-Domain in the Interaction of Factor VII with Tissue Factor - Wildgoose, Peter; Jørgensen, Tony; Komiyama, Yutaka; Nakagaki, Tomohiro; Pedersen, Anders; Kisiel, Walter (Thrombosis and Haemostasis, 1992)
Whether or not the factor VII Gla-domain is involved in the high-affinity interaction of factor VII and tissue factor via calcium-dependent interactions with surrounding phospholipids is unknown. To investigate this, we have purified the factor VII Gla-peptide (FVII-GP) from digested recombinant human factor VII a and assessed its effect on factor VII: tissue factor interactions. FVII-GP inhibited the activation of factor X by factor Vila in the presence of either soluble or cell surface tissue factor halfmaximally at 0.5 μM and 2.7 μM, respectively. However, FVII-GP failed to inhibit the specific binding of factor Vila to cell-surface tissue factor, and did not inhibit the ability of tissue factor to stimulate the amidolytic activity of factor Vila. Unrelipidated tissue factor apoprotein stimulated the amidolytic activity of factor Vila to the same extent as relipidated tissue factor apoprotein. These findings suggest that the factor VII Gla-domain does not directly interact with tissue factor, but rather is important for calcium binding and concomitant expression of other factor VII epitopes necessary for tissue factor recognition and binding. To test this hypothesis, we have prepared a monoclonal antibody against a putative factor VII epitope that participates in the interaction of factor VII with cell-surface tissue factor (peptide 195-206) and assessed its ability to bind to factor VII in the presence and absence of calcium. Binding of this monoclonal antibody (PW-4) to intact factor VII a was calcium-dependent and could be inhibited in a dose-dependent manner by peptide 195-206. The antibody reacted with Gla-domainless factor Vila, but only 37% as compared to intact factor Vila. In addition, PW4 as well as its Fab’ fragment, inhibited factor Vila binding to cell-surface tissue factor. These studies indicate that the factor VII Gla-domain does not provide structural elements that contribute to the formation of a stable factor VII/VII a-tissue factor binary complex. The factor VII Gla-domain appears to be necessary, however, in binding calcium ions and inducing a calcium-dependent conformational change in factor VII/VII a that expresses one or more neoepitopes that participates in the interaction of factor VII/VII a with the extracellular domain of tissue factor apoprotein.